Peningkatan Kualitas Layanan Driver ShopeeFood di Kota Semarang melalui Personal Value dan Kepuasan Kerja dengan Peran Organizational Citizenship Behavior sebagai Mediasi - Satria Afif Naufal Pramudya; Awanis Linati Haziroh; Diana Aqmala; Aries Setiawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study was motivated by the suboptimal quality of ShopeeFood driver services in Semarang, particularly in terms of speed, responsiveness, and consistency of professionalism, amid fierce competition in the food delivery service industry, which indicates internal problems related to driver work behavior. This study aims to analyze the role of personal value and job satisfaction in improving the service quality of ShopeeFood drivers in Semarang City, with Organizational Citizenship Behavior (OCB) as a mediating variable. The study used a quantitative approach with purposive sampling of 120 active ShopeeFood drivers in Semarang City, data collection through a five-point Likert scale questionnaire, and analysis using Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS 4, which included outer model testing, inner model testing, and hypothesis testing. The results show that personal value does not have a significant direct effect on service quality but has a significant effect on OCB, while job satisfaction has a significant effect on both service quality and OCB. Furthermore, OCB has a significant effect on service quality and mediates the effect of personal value and job satisfaction on service quality, where OCB mediation makes the effect of personal value on service quality significant. These findings indicate that improving the service quality of ShopeeFood drivers is more effectively achieved by strengthening job satisfaction and OCB behavior, while personal value provides optimal contributions when manifested in voluntary behavior that supports service quality.